The construction of objects of discourse in the conversational practices of a group of aphasic - Caio Mira (Fórum Linguístico, 2016)
This article aims to analyze excerpts of an interaction between an aphasic group and a non-aphasic group to demonstrate the construction of objects of discourse in conversational situations. To reach that goal, this article’s theoretical approach is based on the textual-interactive Conversational Analysis. The analyzed excerpts prove that the aphasic participants of the group, when inserted in conversational situations, dismiss referential and interactional resources, contributing for the construction of objects of discourse and for the management of the topic. The results obtained from the analyses point out to the linguistic-interactional aspects of the conversational situations of the aphasic group, and not only the linguistic deficit caused by aphasia.